2012
DOI: 10.1371/journal.pone.0036069
|View full text |Cite
|
Sign up to set email alerts
|

Screening Estrogenic Activities of Chemicals or Mixtures In Vivo Using Transgenic (cyp19a1b-GFP) Zebrafish Embryos

Abstract: The tg(cyp19a1b-GFP) transgenic zebrafish expresses GFP (green fluorescent protein) under the control of the cyp19a1b gene, encoding brain aromatase. This gene has two major characteristics: (i) it is only expressed in radial glial progenitors in the brain of fish and (ii) it is exquisitely sensitive to estrogens. Based on these properties, we demonstrate that natural or synthetic hormones (alone or in binary mixture), including androgens or progestagens, and industrial chemicals induce a concentration-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
176
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(198 citation statements)
references
References 49 publications
20
176
2
Order By: Relevance
“…Exposure of the transgenic biosensor of zebrafish to 4-t-OP induced GFP expressed demonstrating that 4-t-OP possesses ability to act as natural estrogen activity in zebrafish [30]. Moreover, exposure to alkylphenol induced GFP expressed in heart of transgenic biosensor zebrafish suggesting 4-t-OP act action in cardiovascular system [31].…”
Section: Discussionmentioning
confidence: 92%
“…Exposure of the transgenic biosensor of zebrafish to 4-t-OP induced GFP expressed demonstrating that 4-t-OP possesses ability to act as natural estrogen activity in zebrafish [30]. Moreover, exposure to alkylphenol induced GFP expressed in heart of transgenic biosensor zebrafish suggesting 4-t-OP act action in cardiovascular system [31].…”
Section: Discussionmentioning
confidence: 92%
“…Specifically, endocrine status has also been widely studied in zebrafish ELS , Andersen et al 2003, Brion et al 2004, Kazeto et al 2004, Muncke and Eggen 2006. Progress in existing in vivo screening of vertebrate gene function has seen the increased use of transgenic and morpholino antisense oligos or gene knockdown technologies (Carvan et al 2005, Hill et al 2005, Hahn and Hestermann 2008, and in particular the induction of green fluorescent protein expression in transgenic zebrafish, cyp19a1b-GFP , Brion et al 2012 and ere-zvtg1: gfp , presenting non-lethal alternatives in animal testing. Furthermore, the zebrafish as a model is a well investigated species with large genetic and genomic resource databases e.g.…”
Section: General Informationmentioning
confidence: 99%
“…The presence of estrogen response element (ERE) in the promoter region of cyp19a1b, but absent on cyp19a1a, has been shown to explain the estrogen-responsiveness of cyp19a1b , Kazeto et al 2001. Thus, being a potential biomarker of estrogenicity, interestingly, the cyp19a1b signal has also been employed in transgenic zebrafish specifically as an estrogenic-sensitive screen , Brion et al 2012. However, in point of fact in vitro gene constructs lack in vivo interactions that are crucial to inherently establish an authentic causal effect.…”
Section: Aromatase and Vitellogenin Transcription Is Affected By Xenomentioning
confidence: 99%
“…Filby et al [11] that showed upregulation of only cyp19a1a but not cyp19a1b in male fathead minnow exposed to EE2, possibly owing to the pronounced expression of the brain isoform (cyp19a1b) in earlier life-stages. The use of cyp19a1b signal has also been employed in transgenic zebrafish specifically as estrogenic-sensitive screens [44,45]. Because cyp19a1b is a key player in steroid biosynthesis at stage of 20dpfZF, involved in conversion of androgen to estrogen, it qualified as a compelling signature of xenoestrogen-induced effects.…”
Section: Exposure I: Selection Of Steroidogenic Endpoint For Xenoestrmentioning
confidence: 99%
“…With as large a sample size (15-25 fish) as in this study, statistically significant difference of estrogenic gene expression between exposures highlights the reliable detection of a genomic signal. Advancement in existing estrogen-sensitive screening has employed the induction of green fluorescent protein expression in transgenic zebrafish, cyp19a1b-GFP [44,45] and ere-zvtg1:gfp [61], pointing to non-lethal alternatives of animal testing. Chen et al [61] showed GFP induction in transgenic zebrafish represented by less than 25% of the exposed fish.…”
Section: Choice Of Suitable Developmental Stage Of Zebrafish For Evalmentioning
confidence: 99%